PENGEMBANGAN INSTRUMEN PENGUKUR TINGKAT KEPUASAN SISWA TERHADAP KUALITAS PELAYANAN PENDIDIKAN DI SEKOLAH - Tata Suharta (Jurnal Evaluasi Pendidikan, 2017)
The purpose of this study is to develop an instrument measuring the level of students satisfaction of educational services quality in the high school. Students satisfaction is the level of a student’s felt state resulting from comparing a product’s perceived performance or outcome in relations to the student’s expectation. Level of the student satisfaction with five dimensions consists of tangible, reliability, responsiveness, assurance, and emphaty. The research sample taken using simple random sampling technique. Development of items based on expert judgement with Likert’s scales. Based on the items which have been selected through the study and validation of expert panelists with interrater reliability coefficient values produced 38 selected items. This instrument has been tested to 200 students of secondary school in Kabupaten Tangerang. Instruments in the research is made in two coulomns respons, consists of performance and expectation. Empirically test through the first and second trials testing through confirmatory factor analysis (CFA) with Maximum Likelihood method (ML) values obtained factor loading above 0,5. From a reliability coefficient calculation shows that the value of multidimensional reliability coefficients more than 0.9 and average variance extracted (AVE) values more than 0.5 in the first and second trials, which means that the level of validity and reliability of the instrument measuring the level students satisfaction of service quality in high school classified as very high. It can be concluded that the level of students satisfaction measuring instrument has good construct validity and reliability.